Reproductive Healthcare in Women with Rheumatoid Arthritis and Psoriatic Diseases in Routine Clinical Practice: Survey Results of Rheumatologists and Dermatologists - Olejárová, Marta; Macejová, Želmíra; Gkalpakiotis, Spyridon; Procházková, Leona; Tóth, Zoltán; Prágr, Pavel (Rheumatology and therapy, 2022)
INTRODUCTION: The proportion of women being treated with biologics is growing. However, data on treatment recommendation awareness among treating physicians and women who are considering pregnancy and family planning are limited. In this study, we used a questionnaire survey to learn how rheumatologists and dermatologists address women's needs for family planning, pregnancy, and breastfeeding, as well as their possible concerns with concurrent inflammatory rheumatic disease or psoriasis. METHODS: A 55-question (in English) survey aimed at identifying surveyed physicians' current practices regarding the reproductive health needs of women with rheumatoid arthritis, psoriasis, or psoriatic arthritis. This survey included 82 rheumatologists and 38 dermatologists from the Czech Republic, Hungary, and Slovakia. RESULTS: The proportion of female patients of reproductive age with the moderate-to-severe disease was 10-30% of all patients treated by the respondents. At the time of diagnosis, approximately two-thirds of the respondents discussed family planning with their patients. Rheumatologists collaborated with other specialists more frequently than dermatologists and gynecologist-obstetricians. Half of the rheumatologists revised systemic treatment 6 months before the patient planned to become pregnant, whereas dermatologists appear to act much sooner. Rheumatologists chose systemic glucocorticoids as the first-line treatment for pregnancy flares, whereas dermatologists chose topical corticosteroids. Congresses and interdisciplinary forums were rated the most valuable sources of information by physicians. CONCLUSIONS: There is a need for more holistic, multidisciplinary, collaborative, and integrated communication between clinicians and women of childbearing age. Physicians should consider the implications of these conditions and medical treatment for women of childbearing age and family planning for those with rheumatoid arthritis and psoriatic disease. Patient-centered care that includes patients' reproductive choices should be a routine clinical practice.
Keywords: Women of childbearing age; Reproductive health; Psoriatic arthritis; Rheumatoid arthritis; Chronic inflammatory disease; Psoriasis; Family planning